Defining the Feature of Cold Wave (Al-Marba'aniyah) in Iraq: Defining the Feature of Cold Wave (Al-Marba'aniyah) in Iraq (Journal of the College of Education for Women, 2019)
Abstract:Al-Marba'aniyah, which is a long cold wave, was defined by ancientIraqis. It represents the coldest days in Iraq. In this research paper, a newscale was put to define it. It shows that the period between the minimumtemperature degree recoded in December and the minimum temperaturedegree recorded in January is considered to be the period of Al-Marba'aniyah.The research concluded that Al-Marba'aniyah is unsteady and it changes inthe days of its occurrence. It was also concluded that the dates of thebeginning and the end of Al-Marba'aniyah are unsteady, too. Moreover, it wasfound out that each of the Siberian high, European high, and finally thesubtropical high are the responsible systems for the beginning and the end ofAl-Marba'aniyah. In addition to this, it was concluded that during the evolutionof Al-Marba'aniyah, the tropical ridge (Geopotential high 500 mb)enormously associates with the surface high pressure and that, during thedecay of Al- Al-Marba'aniyah, the cold troughs enormously associates with thesurface high pressure.